Characterization of sustainable bacterial cellulose fabricated with Vietnamese ingredients for potential textile applications: Tensile and handle properties - Rajkishore Nayak; Donna Cleveland; Frances Joseph (Results in Engineering)
There has been growing demand for biomaterials due to their natural origin, nontoxicity and biodegradability properties. Bacterial cellulose (BC) is one such material with potential for a wide range of applications in medicine, packaging, food, tissue engineering, cosmetics, fashion and textile. This research has attempted to explore the potential of BC in fashion and textile applications fabricated with the indigenous ingredients available in Vietnam. A range of BC samples were fabricated and characterized for various properties such as pH, thickness, areal density, bursting strength, stiffness, drape and crease recovery angle to explore potential applications in fashion and textile. The results showed that the pH of BC samples was mostly acidic, with a pH range of 2.6 to 4.4. Hence, they were treated with commonly available bases to bring the pH within the skin-friendly range for textile applications. Some bursting strength results showed closer values for the textile sample, indicating its potential for textile applications. However, the stiffness and drape values of the BC samples were significantly higher, and crease recovery was significantly lower, indicating its appropriateness for applications where higher stiffness and lower crease recovery properties are desired. Keeping the properties in mind, the authors successfully designed products such as wallets and decorative paintings using the harvested BC samples.